BEHAVIORAL FINANCE IN THE INDONESIAN MSME SECTOR: A SYSTEMATIC LITERATURE REVIEW - Komang Agus Rudi Indra Laksmana (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2026)
This study examines behavioral finance in the Indonesian MSME sector, evaluated using a PRISMA 2020-based SLR. 1,847 articles identified from Web of Science, Google Scholar, ProQuest, SINTA/Garuda, Scopus, and other scientific research sources. 42 peer-reviewed publications satisfied the standards for MMAT and CASP. The review identifies four dominant behavioral finance constructs in the Indonesian MSME sector: overconfidence bias, loss aversion, mental accounting, and herd behavior. These cognitive biases significantly influence financial decision-making, resulting in suboptimal capital allocation, limited adoption of formal financial instruments, and constrained business growth. Digital financial literacy and Islamic financial values operate as contextual moderators unique to the Indonesian setting. This review makes a threefold contribution: it provides the first PRISMA-compliant synthesis of the Indonesian MSME behavioral finance literature (2019–2024); proposes an integrative conceptual framework combining prospect theory, bounded rationality Theora, and social capital theory; and formulates a geographically and methodologically diversified research agenda for future empirical inquiry.